Challenges of health promotion and education strategies to prevent cervical cancer in India: A systematic review - Jissa Vinoda Thulaseedharan; Kirstin Grosse Frie; Rengaswamy Sankaranarayanan (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Although there is a reduction in cervical cancer incidence over the years, it keeps the second position of the most common cancers among females in India. The aim of this review is to understand the challenges of health promotion and education strategies to prevent cervical cancer in India. MATERIALS AND METHODS: This review is based on 78 studies published during 1993-2017 on the topics of awareness, attitude, and acceptance toward cervical cancer, screening, and human papilloma virus vaccination among Indians. The extracted information was summarized according to different populations such as people from different social and community groups, women and men attended clinics, students (nursing/medical/nonmedical), health-care providers (doctors, nurses, and other health workers), migrated Indians, and cervical cancer patients. RESULTS: The awareness about cervical cancer and its prevention was very poor among women from different communities and the majority had a negative attitude toward screening and vaccination in general. The health professionals and medical students were more aware of cervical cancer and its prevention compared to the general population. Majority of students irrespective of medical or nonmedical background had a positive attitude toward vaccination. Only a small proportion of women in the general population were ever screened. CONCLUSIONS: Observations from this review indicate immediate attention of the public health authority to take appropriate actions to educate and motivate general population toward cervical cancer prevention and to improve the facilities to incorporate the much needed preventive and early detection interventions in India.